Two Proclamations by Francisco Xavier Mina: on Heroes and Villains - de Pedro Robles, Antonio E. (Universidad Pedagógica y Tecnológica de Colombia, 2015)
The following article is a relection about certain aspects related to the publication of two political proclamations made by the Spanish military oficer Francisco Xavier Mina, during his incorporation into the Mexican insurgent movement. This study highlights the coniguration of an internationalist liberal historical ideal that turns the independence of American nations into an expansion process of Spain´s own liberal ideology, as well as the construction of a new framework of relations between the mother country and the former American colonies. The two proclamations have beenanalyzed by means of certain models taken from discourse analysis and the theory of interpretation, defended by French philosopher Paul Ricoeur.